2019
DOI: 10.1038/s41598-019-43342-z
|View full text |Cite
|
Sign up to set email alerts
|

Postglacial relative sea level change and glacier activity in the early and late Holocene: Wahlenbergfjorden, Nordaustlandet, Svalbard

Abstract: Sediment cores from Kløverbladvatna, a threshold lake in Wahlenbergfjorden, Nordaustlandet, Svalbard were used to reconstruct Holocene glacier fluctuations. Meltwater from Etonbreen spills over a threshold to the lake, only when the glacier is significantly larger than at present. Lithological logging, loss-on-ignition, ITRAX scanning and radiocarbon dating of the cores show that Kløverbladvatna became isolated from Wahlenbergfjorden c. 5.4 cal. kyr BP due to glacioisostatic rebound. During the Late Holocene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…This would have been facilitated by the higher relative sea level then (Ingólfsson & Landvik 2013; Schomacker et al . 2019; Farnsworth et al . 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This would have been facilitated by the higher relative sea level then (Ingólfsson & Landvik 2013; Schomacker et al . 2019; Farnsworth et al . 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another unknown is the glacioisostatic response to the massive post‐LIA ice mass loss leading to the uplift of the coastal zone. It is widely established that uplifted beaches and marine terraces, so characteristic of Svalbard coastal landscapes record uplift from glacial isostatic adjustment caused by the decay of Svalbard‐Barents Sea Ice Sheet that covered the archipelago during the Last Glacial Maximum (e.g., Forman et al, 2004; Long et al, 2012; Schomacker et al, 2019; Sessford et al, 2015). However, taking into account that the glacier advance during the Neoglacial cooling and the LIA most probably accumulated the largest ice mass during the Holocene in Svalbard (e.g., Farnsworth et al, 2018; Martín‐Moreno et al, 2017; Philipps et al, 2017) the rapid retreat of glaciers observed over the last century may have already overtaken the post‐LGM control of solid Earth motion.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed methodology and full core descriptions and lithostratigraphy are presented by Schomacker et al . (2019) (Kløverbladvatna), Kjellman et al . (2020) (Austre Nevlingen), Voldstad et al .…”
Section: Methodsmentioning
confidence: 99%